Mild Androgen Insensitivity Syndrome presenting in male with infertility and sexual difficulties - Mukhtar, Ahmad Faiq; Ismail, Shaiful Bahari; AK, Azidah; MN, Norhayati; N, Mohd Yunus (Bangladesh Journal of Medical Science, 2023)
Androgen insensitivity syndrome has a wide spectrum of presentations. It results from a mutation in androgen receptor (AR) gene. It ranges from mild androgen insensitivity syndrome (MAIS) which is the mildest form to complete androgen insensitivity syndrome (CAIS). In case of MAIS, the abnormality that can be observed appears to be male infertility and sexual difficulties including premature ejaculation and erectile dysfunction. In this case report, we discuss a case of MAIS in a 37-year-old male who presented with infertility, premature ejaculation, and secondary erectile dysfunction. Bangladesh Journal of Medical Science Vol. 22 No. 02 April’23 Page : 442-444